Allergic sensitization at school age is a systemic low‐grade inflammatory disorder. Issue 7 (17th January 2017) - Chawes, B. L.; Stokholm, J.; Schoos, A.‐M. M.; Fink, N. R.; Brix, S.; Bisgaard, H.
Abstract: Background: Systemic low‐grade inflammation has been demonstrated in a range of the frequent noncommunicable diseases (NCDs) proposing a shared mechanism, but is largely unexplored in relation to allergic sensitization. We therefore aimed to investigate the possible association with childhood allergic sensitization. Methods: High‐sensitivity C‐reactive protein (hs‐CRP), interleukin‐1β (IL‐1β), IL‐6, tumor necrosis factor‐α (TNF‐α), and chemokine (C‐X‐C motif) ligand 8 (CXCL8) were measured in plasma at age 6 months ( N = 214) and 7 years ( N = 277) in children from the Copenhagen Prospective Studies on Asthma in Childhood2000 (COPSAC2000 ) birth cohort. Allergic sensitization against common inhalant and food allergens was determined longitudinally at ages ½, 1½, 4 and 6 years by specific IgE assessments and skin prick tests. Associations between inflammatory biomarkers and sensitization phenotypes were tested with logistic regression and principal component analyses (PCAs). Results: Adjusted for gender, recent infections, and a CRP genetic risk score, hs‐CRP at 7 years was associated with concurrent elevated specific IgE against any allergen [adjusted OR (aOR) = 1.40; 95% CI, 1.14–1.72; P = 0.001], aeroallergens (aOR, 1.43; 1.15–1.77; P = 0.001), food allergens (aOR, 1.31; 95% CI, 1.02–1.67; P = 0.04), sensitization without any clinical allergy symptoms (aOR = 1.40; 1.06–1.85; P = 0.02), and with similar findings for skin prick tests. The other inflammatory markers were not univariately associated with sensitization, but multiparametric PCA suggested a specific inflammatory response among sensitized children. Inflammatory markers at age 6 months were not associated with subsequent development of sensitization phenotypes. Conclusions: Elevated hs‐CRP is associated with allergic sensitization in school‐aged children suggesting systemic low‐grade inflammation as a phenotypic characteristic of this early‐onset NCD.